Stabilization of a Broadly Neutralizing Anti-Chikungunya Virus Single Domain Antibody - Liu, Jinny L.; Webb, Emily M.; Zabetakis, Dan; Burke, Crystal W.; Gardner, Christina L.; Glass, Pamela J.; Legler, Patricia M.; Weger-Lucarelli, James; Anderson, George P.; Goldman, Ellen R. (Frontiers in Medicine, 2021)
A single domain antibody (clone CC3) previously found to neutralize a vaccine strain of the chikungunya virus (PRNT50 = 2. 5 ng/mL) was found to be broadly neutralizing. Clone CC3 is not only able to neutralize a wild-type (WT) strain of chikungunya virus (CHIKV), but also neutralizes WT strains of Mayaro virus (MAYV) and Ross River virus (RRV); both arthralgic, Old World alphaviruses. Interestingly, CC3 also demonstrated a degree of neutralizing activity against the New World alphavirus, Venezuelan equine encephalitis virus (VEEV); albeit both the vaccine strain, TC-83, and the parental, WT Trinidad donkey strain had PRNT50 values 1,000-fold higher than that of CHIKV. However, no neutralization activity was observed with Western equine encephalitis virus (WEEV). Ten CC3 variants designed to possess a range of isoelectric points, both higher and lower, were constructed. This approach successfully identified several lower pI mutants which possessed improved thermal stabilities by as much as 10°C over the original CC3 (Tm = 62°C), and excellent refolding abilities while maintaining their capacity to bind and neutralize CHIKV.